2020
DOI: 10.21203/rs.3.rs-36568/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 induces a unique mitochondrial transcriptome signature

Abstract: SARS-CoV-2 has challenged global healthcare systems in part because its clinical manifestations are heterogeneous. Variable symptoms of SARS-CoV-2 could be attributed to the virus’ ability to mildly induce an innate immune response, as prior transcriptomic data has suggested. Mitochondrial dynamics might partially mediate the effect of SARS-CoV-2 on innate immunity. Many proteins encoded by SARS-CoV have been shown to localize to mitochondria and inhibit Mitochondrial Antiviral Signaling protein (MAVS). We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…94 Preliminary observations suggest that SARSR-CoV-2 affects mitochondrial activity. 95 Furthermore, Wang et al also identified mitochondrial crista abnormalities in liver specimen of COVID-19 patients. 40 Interestingly, impaired mitochondrial activity has also been implicated in the pathogenesis of NAFLD/NASH.…”
Section: Sar S -Cov2 and Hepati C S Te Atos Ismentioning
confidence: 99%
See 1 more Smart Citation
“…94 Preliminary observations suggest that SARSR-CoV-2 affects mitochondrial activity. 95 Furthermore, Wang et al also identified mitochondrial crista abnormalities in liver specimen of COVID-19 patients. 40 Interestingly, impaired mitochondrial activity has also been implicated in the pathogenesis of NAFLD/NASH.…”
Section: Sar S -Cov2 and Hepati C S Te Atos Ismentioning
confidence: 99%
“…Microvesicular steatosis is typically caused by genetic or acquired mitochondrial β‐oxidation defects 94 . Preliminary observations suggest that SARSR‐CoV‐2 affects mitochondrial activity 95 . Furthermore, Wang et al also identified mitochondrial crista abnormalities in liver specimen of COVID‐19 patients 40 .…”
Section: Sars‐cov2 and Hepatic Steatosismentioning
confidence: 99%
“…It is known that impaired mitochondrial activity is associated with the pathogenesis of NAFLD/NASH [119]. Based on transcriptomic analysis and ultrastructural examination, SARS-CoV-2 infection suppressed hepatic mitochondrial activity and caused obvious mitochondrial swelling of hepatocytes [55,120], strongly suggesting that SARS-CoV-2 directly causes cytopathic effects and contributes to MAFLD progression.…”
Section: Direct Cytotoxicity Of Virusmentioning
confidence: 99%
“…Preliminary observations suggest that SARS-CoV-2 affects mitochondrial activity. 57 Furthermore, Wang et al identified mitochondrial crista abnormalities in liver specimens from COVID-19 patients. Interestingly, impaired mitochondrial activity has also been implicated in the pathogenesis of NAFLD/non-alcoholic steatohepatitis.…”
Section: Bilirubin Levelmentioning
confidence: 99%
“…Preliminary observations suggest that SARS‐CoV‐2 affects mitochondrial activity. 57 Furthermore, Wang et al. identified mitochondrial crista abnormalities in liver specimens from COVID‐19 patients.…”
Section: Pathophysiology Of Liver Involvement In Covid-19mentioning
confidence: 99%